Monocyte recruitment during infection and inflammation - Shi, Chao (2011)
Monocytes originate from progenitors in the bone marrow and traffic via the bloodstream to peripheral tissues. During both homeostasis and inflammation, circulating monocytes leave the bloodstream and migrate into tissues where, following conditioning by local growth factors, pro-inflammatory cytokines and microbial products, they differentiate into macrophage or dendritic cell populations. Recruitment of monocytes is essential for effective control and clearance of viral, bacterial, fungal and protozoal infections, but recruited monocytes also contribute to the pathogenesis of inflammatory and degenerative diseases. The mechanisms that control monocyte trafficking under homeostatic, infectious and inflammatory conditions are being unravelled and are the focus of this Review.